Efficiency of high rate treatment of low-strength municipality sewage by a pilot-scale combination system of a sedimentation tank and a down-flow hanging sponge reactor. Issue 16 (16th July 2022) - Kirishima, Yoshihiro; Choeisai, Pairaya; Khotwieng, Watcharapol; Hatamoto, Masashi; Watari, Takahiro; Choeisai, Krit; Panchaban, Piyanuch; Wong-asa, Thotsaphon; Yamaguchi, Takashi
ABSTRACT: Down-flow hanging sponge (DHS) reactor that is sponge-based trickling filter was considered to be an alternative aerobic treatment system for low strength sewage treatment under tropical conditions. This study aims to determine the process performance of the DHS reactor combined with a pre-treatment sedimentation tank (SED) system installed at the municipality sewage treatment plant in Khon Kaen, Thailand over, 1, 600 days. The DHS reactor was operated with three operational periods: low (0.2 kgBODm 3 per day), high (0.5–1.3 kgBODm 3 per day), and super rates (1.7–2.2. kgBODm 3 per day). The results showed effective reductions in biochemical oxygen demand (BOD) and suspended solids by more than 74% and 78%, respectively, during the entire experimental period. Moreover, the final effluent met the Thailand discharge standard with an external short hydraulic retention time of 0.2 h. In addition, the combined system facilitates simultaneous nitrification and denitrification and effectively removed up to 43% of total nitrogen. The self-degradation of the organic compounds occurs owing to the retained sludge in the DHS reactor; this leads to undisputed clogging in sponge media. Therefore, the combined SED-DHS system could be an appropriate sewage treatment system for tropical conditions. GRAPHICAL ABSTRACT: UF0001